Proces dyfuzji innowacji w gospodarce turystycznej - Januszewska, Małgorzata (The Process of Innovation Diffusion in Tourism Economy, 2008)
The basis for the construction of modern tourism economy is created by a common assumption of direct relation between competitive potential of the tourism sector and its ability to create and absorb innovation. The pressure imposed by competition on one hand and technical progress on the other force a tourist enterprise to take up activities aiming at the development of innovative products and processes. The objective of the hereby article becomes an attempt of adapting innovation diffusion aspects in the sector of tourist services.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 2, s. 101-113